Translation and validation of Taiwan Chinese version of the self-regulation questionnaire for gynecologic cancer survivors - Jung-Mei Tsai; Chen-Yuan Hsu; Li-Yun Tsai; Shiow-Luan Tsay (Elsevier, 2019)
Objective: To culturally adapt the self-regulation questionnaire to the Taiwan Chinese version (TC-SRQ) and to evaluate its psychometric properties for gynecologic cancer survivors. Materials and methods: A cross-sectional study was employed with a purposive sample of 287 gynecologic cancer survivors. The TC-SRQ was adapted from a Germany version through back-translation to ensure its quality. For construct validity, confirmatory factor analysis (CFA) was used to assess the TC-SRQ measurement model with fit indexes including the χ2 test, the root mean square error of approximation (RMSEA), and the normed fit index (NFI), the comparative fit index (CFI), and non-normed fit indices (NNFI). For concurrent validity, the Taiwanese version of the European Organization for Research and Treatment of Cancer's 30-item core quality of life (EORTC QLQ-C30) questionnaire was used as a criterion measure for quality of life (QOL). Reliability was evaluated by internal consistency and test-retest reliability. Results: For a modified measurement model of TC-SRQ, the model fit (χ2 = 311.23, P = .0; RMSEA = .088; NFI = .97, CFI = .98, NNFI = .97) was acceptable. The evidence of construct validity of TC-SRQ scale was confirmed by the model estimates. TC-SRQ correlated positively with the global QOL, physical, cognitive, emotional, and social functioning domains, and negatively with fatigue and pain domains of EORTC QLQ-C30. For known groups validity, TC-SRQ was correlated with groups attributed by age, family support, health status, and sleep quality. A Cronbach's α of .91 indicated good internal consistency; the test-retest reliability was .82. Conclusions: TC-SRQ is a valid and reliable instrument for assessing self-regulation in gynecologic cancer survivors. Keywords: Gynecologic cancer survivors, Self-regulation, Quality of life, Psychometrics, Confirmatory factor analysis